2021
DOI: 10.3389/fpsyt.2021.753851
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experience of Healthcare Workers Who Returned to Work After Recovering From COVID-19: A Qualitative Study

Abstract: Background: To date, a large body of literature focuses on the experience of healthcare providers who cared for COVID-19 patients. Qualitative studies exploring the experience of healthcare workers in the workplace after recovering from COVID-19 are limited. This study aimed to describe the experience of healthcare workers who returned to work after recovering from COVID-19.Methods: This study employed a qualitative descriptive approach with a constructionist epistemology. Data were collected through semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…At the moment of returning to work, difficulties can be faced by those who have been affected by COVID-19 and have experienced physical and psychological disturbances as well as the reorganization of work, the loss of productivity, and the reduced ability to work [ 18 ]. In this current scenario, it is important to deeply understand the experience of HCWs affected by COVID-19 who return to work, to support their occupational health and well-being [ 19 , 20 ], and also to identify at-risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment of returning to work, difficulties can be faced by those who have been affected by COVID-19 and have experienced physical and psychological disturbances as well as the reorganization of work, the loss of productivity, and the reduced ability to work [ 18 ]. In this current scenario, it is important to deeply understand the experience of HCWs affected by COVID-19 who return to work, to support their occupational health and well-being [ 19 , 20 ], and also to identify at-risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…This result may be due to the high professionalism and responsibility HCWs assumed for their jobs. The relatively short 2-week period of RTW compared to other reports in the early phase of COVID-19 pandemic may support this supposition [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, it can be assumed that the continuous emotional reaction of pre-professional interns while attending their practice center could have caused a perception that was more focused on their life situation, which is an important indicator of life satisfaction, where they considered themselves lucky compared with the inpatients or the infected staff who are suffering. This is what another study revealed when digging into the experience of health workers in China, who returned to work after recovering from COVID-19 ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 72%